Health Worker Performance and Prevalence of Diarrhoea: A Cross-Sectional Study - Sudirman Sudirman; Saiful Ambodale; Mutmainah Mutmainah; Niluh Desy Purnamasari; Desak Eka Susianawati; Fitri Arni (Environmental Research and Planetary Health, 2025)
Diarrhea has been one of the major health issues, particularly among children, and the performance of healthcare workers in implementing effective diarrhea programs has been crucial for its prevention and treatment. The success of diarrhea control may be influenced by the performance of healthcare workers; however, implementation has remained suboptimal in some areas, including the Marawola Community Health Center, which has experienced fluctuating diarrhea incidence rates. The objective of this study was to analyze the influence of healthcare workers' performance in implementing diarrhea programs on the prevalence of diarrhea cases among children. This study employed quantitative design with a cross-sectional approach, conducted in the service area of the Marawola Health Center in 2024. The study sample consisted of 77 respondents selected using stratified random sampling. Data was collected through questionnaires, and analysis was performed using logistic regression. The results of the logistic regression analysis indicated that the performance of healthcare workers in implementing the diarrhea program significantly affected the incidence of diarrhea in children (p = 0.017), although the constant value was not statistically significant (p = 0.163). This suggests that other factors need to be considered in addition to healthcare worker performance when optimizing the diarrhea program for children. In conclusion, the performance of healthcare workers needs to be improved in the implementation of diarrhea programs for children. Strategies such as training, supervision, the use of technology, and community involvement can be implemented. Further research is needed to explore other factors influencing the effectiveness of these programs.